Bioinformatics for Biologists - Pavel Pevzner [ Editor ] (Cambridge University Press, 2011)
The computational education of biologists is changing to prepare students for facing the complex datasets of today\\\\\\\\\\\\\\\'s life science research. In this concise textbook, the authors\\\\\\\\\\\\\\\' fresh pedagogical approaches lead biology students from first principles towards computational thinking. A team of renowned bioinformaticians take innovative routes to introduce computational ideas in the context of real biological problems. Intuitive explanations promote deep understanding, using little mathematical formalism. Self-contained chapters show how computational procedures are developed and applied to central topics in bioinformatics and genomics, such as the genetic basis of disease, genome evolution or the tree of life concept. Using bioinformatic resources requires a basic understanding of what bioinformatics is and what it can do. Rather than just presenting tools, the authors - each a leading scientist - engage the students\\\\\\\\\\\\\\\' problem-solving skills, preparing them to meet the computational challenges of their life science careers.